TRANSLATION CLASSROOM MANAGEMENT THROUGH PEER ASSESSMENT AND INTERNET BROWSING - I Gst Agung Sri Rwa, Jayantini; I Komang, Sulatra; Putu Chrisma, Dewi (Universitas Pendidikan Ganesha, 2017)
This paper tries to describe the modification of peer assessment and internet browsing as a learning model in translation classroom. It includes the procedures applied in the classroom so that the lecturers in translation class can adopt the model and offer a comprehensive learning situation through the use of peer assessment and internet. The modification is a classroom management strategy to be used in delivering translation course for the English department students. The proposed learning model is encouraged by the benefits of peer assessment (Spiller, 2012).Â and the use of internet in the practice of translating. Here, the modification is expected to create an entirely different atmosphere in translation course.Â The three key points in this paper are classroom management strategy (Brophy in Korpershoek et al., 2014) peer assessment and internet browsing. Peer assessment is combined with internet browsing as the implementation of classroom management strategy with the purpose of providing the English department students an innovative learning model when they join translation course. By innovative, it means that translation course offered to English Department students is not merely centered on the lecturerâ€™s assessment but on peer assessment, which is modified with internet browsing.